Assessing production of the ubiquitous archaeal diglycosyl tetraether lipids in marine subsurface sediment using intramolecular stable isotope probing. (4th October 2012) - Lin, Yu‐Shih; Lipp, Julius S.; Elvert, Marcus; Holler, Thomas; Hinrichs, Kai‐Uwe
Summary The membrane lipids diglycosyl‐glycerol dibiphytanyl glycerol tetraethers (2G‐GDGTs) in marine subsurface sediments are believed to originate from uncultivated benthic archaea, yet the production of 2G‐GDGTs from subseafloor samples has not been demonstrated in vitro. In order to validate sedimentary biosynthesis of 2G‐GDGTs, we performed a stable carbon isotope probing experiment on a subseafloor sample with six different 13C‐labelled substrates (bicarbonate, methane, acetate, leucine, glucose and Spirulina platensis biomass). After 468 days of anoxic incubation, only glucose and S. platensis resulted in label uptake in lipid moieties of 2G‐GDGTs, indicating incorporation of carbon from these organic substrates. The hydrophobic moieties of 2G‐GDGTs showed minimal label incorporation, with up to 4‰ 13C enrichment detected in crenarchaeol‐derived tricyclic biphytane from the S. platensis‐supplemented slurries. The 2G‐GDGT‐derived glucose or glycerol moieties also showed 13C incorporation (Δδ13C = 18–38‰) in the incubations with glucose or S. platensis, consistent with a lipid salvage mechanism utilized by marine benthic archaea to produce new 2G‐GDGTs. The production rates were nevertheless rather slow, even when labile organic matter was supplied. The 2G‐GDGT turnover times of 1700–20 500 years were much longer than those estimated for subseafloor microbial communities, implying that sedimentary 2G‐GDGTs as biomarkers of benthic archaea are cumulative records of past and present generations.